The Privacy Paradox in Luxury Tourism: AI Personalization and Tourist Trust in Indonesian Premium Destinations - Hery Maulana Arif (PT Maju Malaqbi Makkarana, 2026)
The evolution of luxury tourism from material-oriented consumption toward transformative and experiential value has intensified the importance of understanding tourists’ psychological motivations and digital trust in exclusive destinations. Indonesia possesses exceptional cultural and natural assets for luxury tourism; however, research exploring luxury tourist behavior and AI-mediated digital trust within the Indonesian context remains highly limited. This study addresses this gap by investigating the psychological motivations of luxury tourists and examining how AI-driven personalization shapes digital trust and privacy perceptions. Using an exploratory qualitative case study approach, data were collected through semi-structured in-depth interviews with 20 international luxury tourists who had visited exclusive destinations in Indonesia, including Bali, Yogyakarta, Lombok, and Komodo. Thematic analysis revealed four dominant motivational themes: authentic cultural immersion, status affirmation and social signaling, psychological restoration, and transformative self-discovery. The findings also identified a significant “Privacy Paradox,” where tourists simultaneously value AI-based personalized services while expressing concerns regarding data surveillance and privacy intrusion. The study concludes that digital trust in luxury tourism is dynamically negotiated through perceived usefulness, emotional value, and transparency in data governance. Ethical AI implementation and transparent personalization strategies are therefore essential for sustaining long-term trust and competitiveness in Indonesia’s luxury tourism sector.